Relationship between human serum albumin and in-hospital mortality in critical care patients with chronic obstructive pulmonary disease - Ling, Ma; Huiyin, Li; Shanglin, Chen; Haiming, Li; Zhanyi, Di; Shuchun, Wang; Meng, Bai; Murong, Lu (Frontiers in Medicine, 2023)
Background The relationship between human serum albumin levels and the prognosis of critical care patients with chronic obstructive pulmonary disease (COPD) remains controversial. Objective To investigate the relationship between serum albumin levels and in-hospital mortality in critical care patients with COPD. METHODS: This study used a retrospective observational cohort from the Medical Information in Intensive Care database (MIMIC-IV) in the United States. Multivariate Cox regression analysis was used to assess the relationship between serum albumin levels and in-hospital mortality. A restricted cubic spline line was also used to explore nonlinear relationship. Results A total of 3,398 critical care patients with COPD were included. The overall in-hospital mortality was 12.4%. We found a negative relationship between human serum albumin and in-hospital mortality (HR = 0.97, 95% CI 0.96–0.99, p = 0.002). Conclusion In critical care patients with COPD, there was a negative association between human serum albumin and in-hospital mortality.